(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The terms and concepts necessary to work in banking and finance have their own characteristics in each language. The uniqueness of banking and finance terms in English and Uzbek is related to their history, culture and economic systems. Banking and finance terminology in English is often based on international standards. For example, terms such as "interest rate", "loan" and "investment" are widely used in the global financial system. These terms have the same meaning in many countries and facilitate communication in the international financial market.Banking and finance terms in English are often based on the Anglo-Saxon economic system. Finance and banking activities in this system are based on free market principles. Therefore, terms in English are often associated with economic freedom, competition and innovation. Banking and finance terms in the Uzbek language correspond to the characteristics of the Uzbek economic system. In Uzbekistan, the role of the state in the field of banking and finance is large, so terms in the Uzbek language are often associated with state regulation, financial control and economic development. For example, terms such as "government debt" and "financial regulation" are common in the Uzbek language. There are a number of similarities between banking and finance terms in English and Uzbek. Both languages use similar concepts to explain financial processes. For example, the terms "bank", "interest" and "loan" are present in both languages. However, there are also differences. Many terms in English are short and to the point, and their meaning often depends on the context. In the Uzbek language, the terms are more descriptive and can be explained more broadly. For example, terms like "to take a loan" and "to give a loan" are expressed more clearly in Uzbek.